Religious exploration and conversion in forced displacement: a case study of Syrian Muslim refugees in Lebanon receiving assistance from Evangelical Christians - Kraft, Kathryn (Journal of contemporary religion, 2017)
The idea of religious conversion as a break with one's past and a change in identity and belonging is precarious when religious practices are considered in a context of displacement. Forced migrants' sense of identity often becomes volatile when social and political pressures lead them to break with various aspects of their past lives. During a season of displacement, refugees and forced migrants may begin to attend religious meetings of a tradition different to that of their family or cease engaging in religious activities at all. Using the humanitarian engagement of Lebanese Evangelical churches with Syrian Muslim refugees as a case study, this article explores some of the unique dynamics in religious engagement in refugee communities. Many Syrian refugees began to attend church and study Christianity and this did indeed seem to have some sort of spiritual' influence on them, although few considered making a more radical change in their identity.